1997
DOI: 10.1002/(sici)1097-0215(19970822)74:4<433::aid-ijc12>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐67 immunostaining in 322 primary breast cancers: Associations with clinical and pathological variables and prognosis

Abstract: Cell-proliferation markers are very important in the clinical management of cancer patients, and the identification of Ki-67 (a monoclonal antibody that recognizes proliferating cells) can make it easier to define the level of proliferative activity. This study investigated the associations between the Ki-67 levels measured by means of immunohistochemistry, and other clinical and pathological variables and prognosis in 322 breast-cancer patients. A significant association was found (p F 0.001) between Ki-67 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 0 publications
5
29
0
2
Order By: Relevance
“…Twenty-one of 27 studies 45,49,51,55,57,64,70,72,77,83,84,100 -109 showed a correlation with MFS or event free survival, 7 studies after multivariate analysis 49 48,50,59,78,84,102,105,111 We hypothesize that these unexpected results may be ascribed to a statistical bias due to the low number of patients in the current study. A review of the literature concerning p21 showed that 4 of 5 studies correlated p21 with MFS or event free survival, 60,61,87,112 2 studies after multivariate analysis 87,112 ; and 3 of 6 studies 87,88,112 correlated p21 with OS, 2 studies after multivariate analysis.…”
Section: Discussionmentioning
confidence: 58%
“…Twenty-one of 27 studies 45,49,51,55,57,64,70,72,77,83,84,100 -109 showed a correlation with MFS or event free survival, 7 studies after multivariate analysis 49 48,50,59,78,84,102,105,111 We hypothesize that these unexpected results may be ascribed to a statistical bias due to the low number of patients in the current study. A review of the literature concerning p21 showed that 4 of 5 studies correlated p21 with MFS or event free survival, 60,61,87,112 2 studies after multivariate analysis 87,112 ; and 3 of 6 studies 87,88,112 correlated p21 with OS, 2 studies after multivariate analysis.…”
Section: Discussionmentioning
confidence: 58%
“…HR associated with Ki-67 positivity in this case) from studies with inherent dissimilarities. The observed disparity among the conclusions of different studies, responsible for the observed heterogeneity, can be quantified by applying Bukholm et al (2003) 147 No Ceccarelli et al (2000) 217 Yes Galiegue et al (2004) 117 No Gasparini et al (1992) 164 Yes Haerslev et al (1996) 487 Yes Jalava et al (2000) 414 No Kroger et al (2006) 157 No Kronblad et al (2006) 377 Yes Lampe et al (1998) 142 Yes Liu et al (2000) 225 Yes Michels et al (2003) 104 No Molino et al (1997) 322 Yes Rudas et al (1994) 184 No Tsutsui et al (2005) 249 Yes Yang et al (2003) 147 No…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this is unrealistic at the individual level, since it suggests that patients, who have tumors with Ki-67 levels close to the cut-point but on either side of the cut-point, are very different, and in turn receives different therapy, whereas in reality they are probably very similar. Few investigators specifically directed their analysis to Ki-67 cut-off values but failed to individuate a single optimal value, while demonstrating a linear association between increasing staining counts and poorer outcome (Molino, 1997). We adopted the similar approach as proposed by the St. Gallen International Expert Consensus using 2 cuff points at 15% and 30%, subcategorizing Ki67 level into low, high and an intermediate risk category.…”
Section: Discussionmentioning
confidence: 99%